Post-Operative Prognosis of the Patients with Esophageal Atresia: The 22-Year Experience of a Reference Hospital - BAKAL, U.; ERSOZ, F.; SARAC, M.; AYDIN, M.; TARTAR, T.; ORMAN, A.; KAZEZ, A. (Medcom Ltd, 2022)
Introduction: To investigate the post-operative prognosis of newborns with esophageal atresia (EA). Methods: Patients operated for EA were classified according to their gestational age, birth-weight, gender, and study period (1996-2006 & 2007-2017), type of atresia, accompanying additional anomaly and Waterston risk categories. Results: Of the 87 cases, 87.4% had EA + distal tracheoesophageal fistula, 11.5% had isolated EA and 1.1% had isolated tracheoesophageal fistula. While 36.8% patients developed post-operative complications, 37% patients died. There was a statistically significant difference between full-term and preterm newborns in terms of mortality rate (p<0.05). Most of dead cases had low birth-weight of <2500 g (n=28/55). Mortality rates of the patients with EA according to two study periods were 57% and 22%, respectively. Main causes of mortality were sepsis (n=17), pneumonia (n=9), and respiratory failure (n=6). Mortality rate among those had accompanying additional anomaly was 84.4% (p<0.05). There was a significant difference between Waterston's risk classification (Groups C and B) and post-operative complication, and mortality rates (p<0.05). In those surviving cases, the most common long-term complication was dysphagia (83%). Conclusion: Morbidity and mortality rates of patients with EA in developing countries like to our study are still high. Low birth-weight, accompanying additional anomaly, Waterston Groups C and B, and post-operative complications are the most important causes of mortality. Waterston's risk classification is a good predictor of the prognosis in patients with EA.
Keywords: Classification; Esophageal atresia; Mortality; Prognosis; Surgery; Tracheoesophageal fistula